The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1515/revneuro-2012-0055
|View full text |Cite
|
Sign up to set email alerts
|

A role for the superior colliculus in the modulation of threat responsiveness in primates: toward the ontogenesis of the social brain

Abstract: Defense and social mechanisms in primates seem to share, at least in infancy, common neural substrata.Among these, recent research has implicated the primate superior colliculus (SC) on tasks involving visual detection and recognition of threatening stimuli, such as snakes and faces with emotional expressions. There is also evidence that both kinds of stimuli share specific characteristics and command special attention in the primate visual system. The present review focuses on the role of the SC in these seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 0 publications
6
25
0
Order By: Relevance
“…Taken together, these findings suggest that SC malfunctioning and/or malformation might be related to the origin and development of autism. Consistent with this idea, bilateral SC lesions induced deficits in social behaviors in infant monkeys [26], and relations between anatomical disturbance in the SC and social and cognitive deficits in autism have been suggested in rats [27]. Along with these previous studies, the present data suggest that the SC is a compelling target for the investigation of attentional deficits in autism.…”
Section: The Role Of the Sc In Attentional Deficits In Autismsupporting
confidence: 89%
“…Taken together, these findings suggest that SC malfunctioning and/or malformation might be related to the origin and development of autism. Consistent with this idea, bilateral SC lesions induced deficits in social behaviors in infant monkeys [26], and relations between anatomical disturbance in the SC and social and cognitive deficits in autism have been suggested in rats [27]. Along with these previous studies, the present data suggest that the SC is a compelling target for the investigation of attentional deficits in autism.…”
Section: The Role Of the Sc In Attentional Deficits In Autismsupporting
confidence: 89%
“…Similarly, studies have shown that the superior colliculus, another structure involved in the control of ToM, is implicated in the visual detection and recognition of threatening stimuli such as snakes and faces with emotional expressions (Maior et al 2012). This overlap in function is most pronounced during infancy, a finding also in line with the present hypothesis as TI and IS are also more pronounced in immature individuals.…”
Section: Eye Contact and Threatsupporting
confidence: 89%
“…These results support previous studies that demonstrated the importance of such structures in PPI [3], [14]. Although SC is involved in responses to visual stimuli, including detection of salient stimuli, head and eyes orientation, saccadic movements and shifts of attention [15][20], this subcortical structure is strongly implicated in defensive behaviours [21][24]. In addiction, SC receives auditory inputs from inferior colliculus [25] that must be related to PPI [13].…”
Section: Introductionsupporting
confidence: 90%